2015
DOI: 10.1007/s11356-015-5446-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved traceability of Shiga-toxin-producing Escherichia coli using CRISPRs for detection and typing

Abstract: Among strains of Shiga-toxin-producing Escherichia coli (STEC), seven serogroups (O26, O45, O103, O111, O121, O145, and O157) are frequently associated with severe clinical illness in humans. The development of methods for their reliable detection from complex samples such as food has been challenging thus far, and is currently based on the PCR detection of the major virulence genes stx1, stx2, and eae, and O-serogroup-specific genes. However, this approach lacks resolution. Moreover, new STEC serotypes are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 94 publications
(116 reference statements)
0
2
0
Order By: Relevance
“… Delannoy et al (2013a , b , 2016b ) have already demonstrated that individual combinations of an extended set of known markers beyond the classical STEC marker genes allow the identification of STEC serotypes (O157:H7, O26:H11, O45:H2, O103:H2, O111:H8, O121:H19, O145:H28, and their non-motile derivatives), which are most frequently implicated in outbreaks and sporadic cases of hemorrhagic colitis and hemolytic uremic syndrome worldwide. Additionally they showed that clustered regularly interspaced short palindromic repeat (CRISPR) regions can be used to discriminate the same serotypes as well as O104:H4 ( Delannoy et al, 2012a , b , 2016a ). Furthermore, Wong et al (2014) identified a novel O157:H7-specific marker in a genome wide insertion/deletion-based approach.…”
Section: Discussionmentioning
confidence: 99%
“… Delannoy et al (2013a , b , 2016b ) have already demonstrated that individual combinations of an extended set of known markers beyond the classical STEC marker genes allow the identification of STEC serotypes (O157:H7, O26:H11, O45:H2, O103:H2, O111:H8, O121:H19, O145:H28, and their non-motile derivatives), which are most frequently implicated in outbreaks and sporadic cases of hemorrhagic colitis and hemolytic uremic syndrome worldwide. Additionally they showed that clustered regularly interspaced short palindromic repeat (CRISPR) regions can be used to discriminate the same serotypes as well as O104:H4 ( Delannoy et al, 2012a , b , 2016a ). Furthermore, Wong et al (2014) identified a novel O157:H7-specific marker in a genome wide insertion/deletion-based approach.…”
Section: Discussionmentioning
confidence: 99%
“…The industrial relevance of CRISPR-based genotyping has been demonstrated in several bacterial species widely found in the food supply chain, encompassing starter cultures and food spoilage organisms such as Streptococcus thermophilus [14], Bifidobacterium longum [15], and Lactobacillus buchneri [16]. CRISPR-based genotyping also exhibits significant medical relevance through its usage in identification of pathogens such as Mycobacterium tuberculosis [17,18], Salmonella enterica [19,20], Clostridium difficile [21], Escherichia coli and many others [22,23], including food-borne pathogens. Characterization of CRISPR-Cas systems has also revealed alternative functions such as roles in virulence regulation and DNA repair [24].…”
Section: Introductionmentioning
confidence: 99%